A CASE STUDY ON STUDENTS ABILITY IN READING SUMMARY OF DESCRIPTIVE TEXT - Mohammad Maghfur (LPPM IAI QOMARUDDIN GRESIK, 2019)
Teaching English consist of four language skill, they are: listening, speaking, reading and writing. The writer limits the reseach by choosing one of the aspects is reading. Teaching English reading is one of the important components in learning English. However, many students still have difficulties in understanding the English, because the students think that English is difficult. The role of this component can measure the students‟ability in reading summary whether their ability is high, fair and low.The purposes of this research are to examine the students‟ ability in reading summary. The students‟ ability refers to the students‟ ability in reading summary if the students write based on the component of good summary are main idea, facts, context, grammar, structure, Panctuacion and conclusion.The researcher used qualitative descriptive in this research, because the researcher know because it is explored the role of summarizing in facilitating the school of summary reading ability. Based on the preliminary reseach there was a tendency that they have difficulties in understanding the reading text. There is in seventh grade the students are to have dificulties in understanding English reading text becouse there scores are less than the minimum passing standart (school‟s KKM). Therefore these students will be given a test to find out their difficulties in understanding the text.This research will also identify some useful criteria for profiling students‟ summary reading ability.Keyword: Reading Summary, Descriptive Text